FEASIBILITY ANALYSIS OF TILAPIA FISH FARMING IN FLOATING NET CAGES (KJA) IN LAKE RANAU - Emilyasari, Desy; Tarigan, Rani Rehulina; Diniariwisan, Damai (Journal of Agriculture, 2023)
Lake Ranau is located on the border of West Lampung Regency, Lampung Province and South Ogan Komering Ulu Regency, South Sumatra Province. Lake Ranau has functions including ecological and socio-economic cultural functions. Some important technical       aspects in a tilapia aquaculture business in KJA include KJA components, maintenance/production processes ranging from seed stocking, feeding to harvesting and constraints faced by farmers during the production process. The criteria observed in determining the feasibility of tilapia KJA cultivation include: investment costs, profits, profitability, BEP (Break Event Point) and R / C Ratio (Revenue Cost Ratio). Economically, tilapia aquaculture in KJA in the waters of Lake Ranau is profitable and feasible for both category I and category II. The profitability value of this KJA farming business is 115% for category I and 119% for category II. The R/C ratio value in one production cycle is 2.15 for category I and 2.19 for category II which means the business is feasible to establish.